Evaluation of fermented milk containing probiotic on dental enamel and biofilm: In situ study - Lodi, Carolina Simonetti [UNESP]; Manarelli, Michele Mauricio [UNESP]; Sassaki, Kikue Takebayashi [UNESP]; Fraiz, Fabian Calixto; Delbem, Alberto Carlos Botazzo [UNESP]; Rodrigues Martinhon, Cleide Cristina [UNESP] (Pergamon-Elsevier B.V. Ltd, 2010)
Objectives: The aim of this study was to in situ evaluate the pH before and after the application of the fermented milk product; the fluoride (F), calcium (Ca), phosphate (P), and insoluble extracellular polysaccharides (EPS) concentration on the dental biofilm; the demineralisation of the bovine dental enamel.Design: Ten volunteers wore palatine devices containing four blocks of bovine dental enamel during three phases of 14 days each. in each phase, the treatment was accomplished with either fermented milk A (Yakult(R)), or 20% sucrose solution (control) or fermented milk B (Batavito(R)). Then, dental biofilm was collected, processed and the ionic concentration and insoluble extracellular polysaccharides appraised. For evaluation of the mineral loss, both the initial and final microhardness were determined.Results: The results showed that the ionic concentration (F, Ca and P) was significantly higher in the fermented milk B in comparison with both the fermented milk A and the 20% sucrose solution. There was no significant difference amongst these last two. With regarding EPS was significantly lower in fermented milk B compared to fermented milk A and sucrose (P < 0.05), without significant difference amongst these last two. The two experimental groups did not differ significantly but had smaller mineral losses than control group.Conclusion: It was concluded that all treatment decreased the pH of dental biofilm and promoted demineralisation of the enamel, although fermented milk B presented the lowest EPS content and percentage change and integrated loss of surface hardness. More studies should be developed to evaluate the action of probiotics on the bacterial activity and its interference on demineralisation, once the literature has been showing probiotics as a promissory caries reducing agent. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Milk fermentation; Probiotics; Dental decay; Demineralisation